Alfred Schutz’s main contributions to the field of economic reflection - López, Daniela Griselda (SocietàMutamentoPolitica, 2016)
For several decades, contemporary social theory has held a considerable misunderstanding around phenomenologically oriented sociology, which has undermined its heuristic potential and, as a consequence, has pushed its conclusions to a marginal place in current discussions. In contrast, our article aims to recover that hermeneutical framework in order to think economic phenomena such as the economic action and the order of the market processes. It is undeniable that Alfred Schutz’s work provides theoretical and methodological elements for the sociological analysis of the economic world. The linkages between Schutz- ian sociology and economic reflection vary widely, ranging from his formative stage within the context of the Mises Circle to the current recovery of his work by Economic Sociology. Within this framework, the aim of this work is to summarize Schutz’s main contributions to the field of economic reflection. The recovery and systematization of the Schutzian vocabulary -in the interface between sociology and economics- can contribute with new elements not only to think from a theoretical point of view but also to address economic phenomena empirically.